POTENSI EKSTRAK DAUN PINUS (Pinus merkusii Jungh. et de Vriese) SEBAGAI BIOHERBISIDA PENGHAMBAT PERKECAMBAHAN Echinochloa colonum L. DAN Amaranthus viridis. - Yusuf Andi Senjaya; Wahyu Surakusumah (Forestry Faculty of Universitas Hasanuddin, 2008)
The allelopathic substances are organic agents which are produced and released by a plant that cause alteration on the neighboring plants. The characteristics of allelochemicals usually inhibit germination of other species and sometime will reduce growth of the other species which associate with the producer of allelochemicals. The mechanism of allelochemicals can be used to suppress a germination of Echinochloa colonum L. and Amaranthus viridis L. These plants are weeds species of rice. The aims of this research were to study the allelochemicals effect from the leaf of pines (Pinus merkusii Jungh. et de Vriese) on germination of Echinochloa colonum L. and Amaranthus viridis L.. The experimental design used Completely Randomized Design with five replicates for each concentration (0, 250, 500, 750, 1000 ppm). The result which was analyzed with One-Way Analyze of Varians (ANOVA) indicated that giving a pine leaf extracts had an inhibitor effect on germination of E. colonum L. and A. viridis L. Keywords: Pinus merkusii Jungh. et de Vriese, allelopathy, weeds, Echinochloa colonum L., Amaranthus viridis L. References